A comparative study of the Constitutionality criterion in the modern state and the Islamic Republic of Iran - Ali-Akbar Gorji; mohammadshahab jalilvand (دولت‌پژوهی, 2019)
Islamic Republic of Iran is a state with unique features in the present time that the matching characteristics with the characteristics of the modern state, there are many opinions dispersed. The modern state, which has its roots in the history of the West, has 10 features that distinguish it from pre-modern states. Meanwhile, the Constitution is an essential characteristic of the modern state That means adherence to the constitution. Therefore, the theory of constitutional government emphasizes that the the government is basically guardian of order based on the constitution 's power structure and the structure of power in all its aspects should be based on the constitution. This article tries to comment on the constitutional criteria, in the characteristics of the modern state, and the state's political power structure in the Islamic Republic of Iran in this respect will be reviewed and concludes that although in cases such as: the structure of representation, separation of powers, rule of law and the judicial process of securing the Islamic Republic of Iran, there are roots of the development of a governance structure based on the constitution, but with a little reflection on some of the principles of the constitution and also delving into some practice, it is observed that in the context of community governance, constitutional ambiguities of criteria has occurred.